Changes in the urban morphology of yolombó, a small village in antioquia’s mountains, colombia (2009)
This paper presents an exercise of urban morphology in Yolombó, a small village on the precipitous northwestern mountains of Antioquia, Colombia. It intends to make a historical journey that accounts for the most important changes of this town both in the configuration of its urban shape as well as in the modifications to its architectural typology. A permanent reference to the settlement’s location, situation and its historical function as a passing town, along with the understanding of socioeconomic and demographic factors, will be the core interpretation themes of a research proposal for the study of small towns in Colombia. This essay intends to contribute and encourage the research on urban morphology in Colombia —a little-developed field in this country—, taking up the approaches of geographers like Peirce Lewis, who uses elements from cultural geography in his studies of spaces different from big cities’ landscapes.